Public Comments on Proposed Regulatory Reforms That Would Impact Biospecimen Research: The Good, the Bad and the Puzzling - Cadigan, R. Jean (IRB, 2015)
The regulations governing human subjects research (45 CFR 46) remain largely unchanged since their adoption. As a first step in their revision, the federal government published the Advance Notice of Proposed Rule Making (ANPRM) in 2011. The public responded with over 1100 comments. We selected a random sample of 300 comments, examining whether they addressed biospecimen research in terms of views on mandated consent, waivers of consent, use of a short general consent form, or identifiability of biospecimens. We conducted content analysis on the 109 comments that fulfilled these criteria Findings reveal little support for the proposal to mandate consent, strong support for the current waiver system, confusion about use of a standard general consent form, and disagreement about the implications of biospecimen identifiability. As the government moves ahead in its rulemaking process, it is important to consider what the public comments reveal about support and/or concerns for proposed changes.